Anoctamins and gastrointestinal smooth muscle excitability - Sanders, Kenton M. (2011)
Interstitial cells of Cajal (ICC) generate electrical pacemaker activity in gastrointestinal (GI) smooth muscles. We investigated whether Tmem16a, which encodes Anoctamin 1 (ANO1), a Ca(2+)-activated Cl(−) channel might be involved in pacemaker activity in ICC. Tmem16a transcripts and ANO1 were expressed robustly in GI muscles, specifically in ICC in murine, non-human primate (Macaca fascicularis) and human GI tracts. Splice variants of Tmem16a are expressed in GI muscles, as well as other paralogues of the Tmem16 family. Ca(2+)-activated Cl(−) (CaCC) channel blocking drugs, niflumic acid and 4,4′-diisothiocyano-2,2′-stillbene-disulfonic acid (DIDS), blocked slow waves in intact muscles of mouse, primate, and human small intestine and stomach. Slow waves failed to develop in Tmem16a knock-out mice (Tmem16a(tm1Bdh)(/)(tm1Bdh)). The pacemaker mechanism was investigated in isolated ICC from transgenic mice with constitutive expression of copGFP. Depolarization of ICC activated inward currents due to a Cl(−) selective conductance. Removal of extracellular Ca(2+), replacement of Ca(2+) with Ba(2+), or extracellular Ni(2+) (30 μm) blocked the inward current. Single Ca(2+)-activated Cl(−) channels with a unitary conductance of 7.8 pS were resolved in excised patches from ICC. The inward current was blocked in a concentration-dependent manner by niflumic acid (IC(50) = 4.8 μm). The role of ANO1 in cholinergic responses in ICC was also investigated. CCh activated Ca(2+)-activated Cl(−) currents in ICC, and responses to cholinergic nerve stimulation were blocked by niflumic acid in intact muscles. ANO1 is a prominent conductance in ICC and these channels appear to be involved in pacemaker activity and in responses to enteric excitatory neurotransmitters.